Critical Alliances - Cameron, S. Brooke (University of Toronto Press, 2021)
Critical Alliances argues that late-Victorian and modernist feminist authors saw in literary representations of female collaboration an opportunity to produce new gender and economic roles for women. It is not often that one thinks of female allegiances – such as kinship networks, cultural inheritance, or lesbian marriage – as influencing the marketplace; nor does one often think of economic models when theorizing feminist cooperation. S. Brooke Cameron suggest that, through their representations of female partnership, feminist authors such as Virginia Woolf, Olive Schreiner, George Egerton, Amy Levy, and Michael Field redefined the gendered marketplace and, with it, women’s professional opportunities.